Inhibition of phosphodiesterase 10A by MP-10 rescues behavioral deficits and normalizes microglial morphology and synaptic pruning in a mouse model of FOXP1 syndrome - Fröhlich, Henning; Wang, Jing; Althammer, Ferdinand; Schubert, Tim; Kluck, Nina; Grinevich, Valéry; Mellein, Stefanie; Schaaf, Christian P.; Rappold, Gudrun (Advanced science, 2025)
FOXP1 syndrome caused by FOXP1 haploinsufficiency is characterized by intellectual disability, speech, and language impairment, autistic features, and neuropsychiatric abnormalities such as anxiety and hyperactivity. Behavioral changes in patients are mirrored in Foxp1± mice. It is shown that decreased Foxp1 in the Foxp1± striatum results in a significant decrease in phosphodiesterase 10a (Pde10a). Predominantly expressed in medium spiny neurons (MSNs), Pde10a modulates basal ganglia circuitry. Furthermore, the Foxp1± striatum exhibits microglial activation, reduced synaptic pruning, and dysregulation of 111 inflammatory genes. These include the downregulated P2ry12 and Fcrls, markers of homeostatic microglia, and upregulated Cd74, a marker of reactive microglia, suggesting that neuroinflammation contributes to the observed deficits. Interestingly, treatment of Foxp1± mice with the PDE10A antagonist MP-10 (PF-2545920) immediately after birth not only corrects behavioral abnormalities, including decreased ultrasonic vocalization, hyperactivity, and anxiety but also normalizes changes in microglia morphology and synaptic pruning. Transcriptomic analysis with a neuroinflammation-specific gene panel reveals nominal gene expression changes after MP-10 treatment, including Bdnf upregulation and enrichment of neurotrophin signaling. Since FOXP1 and its signaling pathway are highly conserved, administration of MP-10 or other Pde10a antagonists may also alleviate the neurological dysfunction seen in humans with FOXP1 syndrome.
Erstmals veröffentlicht: 26. Juni 2025
Gesehen am 25.09.2025